Kajian Termal Akibat Paparan Panas dan Perbaikan Lingkungan Kerja - Listiani Nurul Huda; Kristoffel Colbert Pandiangan (Institute of Research and Community Outreach - Petra Christian University, 2012)
This study aims to analyze thermal condition and improve working environment by designed ventilation systems due to improve air circulation and reduce heat exposure occurred so that workers feel more comfortable working. This study describes the thermal conditions of work and its relation to psychological aspects operator traced through thermal questionnaires. By knowing the conditions of the proposed design is further improved ventilation system. The measurement results show that the thermal average air temperature in the formulations room was 31.7 °C and wind speed of 0.27 m/s. Heat Stress Index (HSI) in the workplace about 94.41%, which indicates the great potential of the dangers of heat stress. Wet Bulb Globe Temperature (WBGT) index gained 27.64 °C so that the percentage of working time and rest time workers was 6.55 and 1.55 hours, where the percentage is not according to the standard. Productive work time workers only achieved ranged from (76.58 ± 5.91)%, where the figure is still below the standards of the company. Simulation with Computer Fluid Dynamic (CFD) software shows actual workplace conditions are very hot and poorly ventilated. By conducting some simulations improvement, then found a comfortable room conditions and air circulation smoothly. Thermal comfort is finally concluded comfortable room after Cv’s room obtained exceeds 0.34 m/s in accordance with the Macfarlane theory’s.